2020
DOI: 10.3390/en13102518
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Corrosion Rates for Offshore Wind Turbines with Depth in the North Sea

Abstract: Corrosion in the marine environment is a complex and expensive form of damage. It is commonly studied by the deployment of coupons that reflect the marine corrosion a structure will experience, thus allowing design and maintenance prevention strategies to be developed accordingly. This study stems from the lack of information in the literature regarding the profiling of corrosion with respect to marine depth in the North Sea where important wind farm developments have been undertaken. To address such issue a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Different reasons can be identified behind the growth of corrosion process in an offshore structure, such as temperature, salinity, pH, and coating damage due to tidal fluctuations, dissolved oxygen, variable cyclic load due to wave and wind impact, etc. [17].…”
Section: Structural Health Monitoring Of Wind Turbines: Corrosion Monitoringmentioning
confidence: 99%
“…Different reasons can be identified behind the growth of corrosion process in an offshore structure, such as temperature, salinity, pH, and coating damage due to tidal fluctuations, dissolved oxygen, variable cyclic load due to wave and wind impact, etc. [17].…”
Section: Structural Health Monitoring Of Wind Turbines: Corrosion Monitoringmentioning
confidence: 99%
“…In both atmospheric and immersed conditions, carbon steels mainly corrode uniformly, with a homogeneously distributed metal loss over the surface. However, localized corrosion may also develop on a surface initially corroding uniformly (Khodabux et al, 2020), explained due to effects from biological organisms in the sea water and the built-up of corrosion products. Non-uniform corrosion mechanisms happen when the electrochemical cell is distributed in an abnormal way over the surface of the metal, such that anodic and cathodic sites differ in size, resulting in an accelerated localized loss of metal and the formation of cavities and holes.…”
Section: Corrosion Mechanismsmentioning
confidence: 99%
“…Although the individual impacts of these factors on corrosion are well understood, the combined influence of these factors together are complicated and unknown. According to the work done by (Khodabux et al, 2020), some examples about corrosion rates from different locations are shown in Table 2.…”
Section: Corrosion Rate Determinationmentioning
confidence: 99%